2008
DOI: 10.1007/s00531-008-0387-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of highly saline fluids in siliciclastic sequences: genetic implications for post-Variscan fluid flow in the Moravosilesian Palaeozoic of the Czech Republic

Abstract: Ubiquitous post-Variscan dolomites occur in Zn-Pb-Cu veins at the Nízký Jeseník Mountains and the Upper Silesian Basin (Lower and Upper Carboniferous siliciclastics at the eastern part of the Bohemian Massif).Crush-leach, stable isotope (oxygen and carbon) and microthermometry analysis of the fluid inclusions in dolomites enable understanding the geochemistry, origin and possible migration pathways of the fluids. Homogenisation temperatures of fluid inclusions range between 66 and 148°C, with generally higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…According to [98] the origin of this type of fluid responsible for the genesis of some post-Variscan mineralization in Sardinia is mainly from evaporated seawater, with a possible small contribution from halite dissolution. Post-Variscan brine associated to the deposition of dolomite in Zn-Pb-Cu veins at the Nızky Jesenık Mountains and the Upper Silesian Basin (Czech Republic) are also interpreted as evaporated sea-water [103]. Whereas, [96] suggested that the mixing of post-Variscan NaCl-CaCl2-bearing basinal brines with low-temperature sulphate-rich formation waters can explain the temperature/salinity features of fluid inclusions from post-Variscan mineralization of the Harz (Germany) mining district.…”
Section: Discussionmentioning
confidence: 99%
“…According to [98] the origin of this type of fluid responsible for the genesis of some post-Variscan mineralization in Sardinia is mainly from evaporated seawater, with a possible small contribution from halite dissolution. Post-Variscan brine associated to the deposition of dolomite in Zn-Pb-Cu veins at the Nızky Jesenık Mountains and the Upper Silesian Basin (Czech Republic) are also interpreted as evaporated sea-water [103]. Whereas, [96] suggested that the mixing of post-Variscan NaCl-CaCl2-bearing basinal brines with low-temperature sulphate-rich formation waters can explain the temperature/salinity features of fluid inclusions from post-Variscan mineralization of the Harz (Germany) mining district.…”
Section: Discussionmentioning
confidence: 99%
“…The 'basement brines' are H 2 O-Ca-NaCl-dominated fluids with high salinities up to halite saturation due to evaporation in a marine environment. Homogenisation temperatures of B200°C are distinctly lower as compared to the metamorphic Variscan fluids (Behr et al 1987;Heijlen et al 2001;Kucera et al 2010).…”
Section: Regional Geology and Fluid Evolutionmentioning
confidence: 95%
“…Numerous, well-known hydrothermal veins, occurring in the Nízký Jeseník Mts., are a record of fluid influence on the Culm rocks. These polymetallic veins are concentrated in historical mining districts, where mainly silver and lead and also gold were mined (Fojt and Vecera, 2000;Kuèera and Slobodnik, 2002;Zimák et al, 2002;Kuèera et al, 2010;Dolníèek et al, 2014;Janiková et al, 2015). Common ore minerals are galena, sphalerite, chalcopyrite, pyrite and marcasite, whilst quartz, Mg, Fe-carbonates, calcite and barite represent gangue minerals.…”
Section: Thermal Evolution Of the Moravo-silesian Fold And Thrust Beltmentioning
confidence: 99%
“…Previous studies on fluid inclusions in the Culm Basin (Zimák et al, 2002;Kuèera et al, 2010;Dolníèek et al, 2014) focused on veins associated with ore mineralisation. Their homogenisation temperatures are considerably lower than those of samples CZ9, CZ74 and SV.…”
Section: Fluid Inclusionsmentioning
confidence: 99%